Hypoglycemic and Antihyperglycemic Effects of Different Extracts and Combinations of Withania coagulans Dunal and Acacia arabica Lamk in Normal and Alloxan Induced Diabetic Rats - Yasir, Mohammad; Shrivastava, Rahul; Jain, Preteek; Das, Debajyoti (Pharmacognosy Communications)
Introduction: Acacia arabica and Withania coagulans commonly known as babool and paneer phool respectively are used in traditional Indian medicine for treatment of diabetes mellitus. Methods: The hypoglycemic effect of aqueous extracts (hot and cold water) and hydroalcoholic extract of Acacia arabica and Withania coagulans was investigated. Oral administration of a cold water extract of Acacia arabica bark, and a hydroalcoholic extract of Withania coagulans to diabetic and normal rats at a dose of 400 mg/kg body weight resulted in a significant reduction of blood glucose, cholesterol and triglycerides in alloxan induced diabetic rats. Results: Phytochemical investigation found that saponins, flavonoids, alkaloids and tannins were present in the Withania coagulans extracts, and phenolic compounds were presents in Acacia arabica extracts. The hydroalcoholic extract of Withania coagulans, and the cold water extract of Acacia arabica were found to reduce the blood-glucose level to normal level within seven days. Promising effects were observed when a combination of both extracts was administered to the test animals. Histological studies of the β-cells indicate that the extracts affect pancreatic cells. Conclusions: The hydroalcoholic extract of Withania coagulans and the cold aqueous extract of Withania coagulans exhibited antihyperglycemic activities in alloxan-induced diabetic rats. Combination of both plants in the ratio 400+400 mg/kg shows higher antihyperglycemic activities. Regereneration of β-cells, is seen in combinations of extract of both the plants.
Keywords: Withania coagulans; diabetes mellitus; Acacia arabica; combinations